Acupressure and Decrease Pain Menstruation (Dysmenorrhea Primary) - Tuti Sukini; Tri Wiji Lestari; Mundarti Mundarti (Jurnal Riset Kesehatan, 2012)
The purpose of this study was to determine the effectiveness of therapy akupressur to the reduction of menstrual pain / dysmenorrhea primary. Research design is a quasi-experimental study. The sample consistedof 160 respondents who experienced primary dysmenorrhea. The data obtained were analyzed using Wilcoxon statistical test test Test Match Pairs. The data showed significant value is 0000 (p less than 0.05), it can be concluded thatthere is a difference between pain before therapy akupressur with action after acupressure.